PENGEMBANGAN MEDIA KOMIK INTERAKTIF UNTUK MENINGKATKAN KEMAMPUAN LITERASI BACA SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS III SD INPRES 2 MARIA - Afrinah; Muh. Rijalul Akbar; Mirham Nurul Hairunis (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop and evaluate the effectiveness of interactive comic learning media to improve reading literacy skills of third-grade students at SDN Inpres 2 Maria in the Indonesian Language subject. Reading literacy is an essential skill that supports learning success, and the use of engaging learning media is believed to enhance students’ motivation and learning outcomes. This research employs a Research and Development (R&D) method using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The study population consists of third-grade students at SDN Inpres 2 Maria, with a small group trial (10 students) and a large group trial (20 students). Data were collected through expert validation questionnaires, teacher and student responses, as well as reading literacy tests (pre-test and post-test). The results of media and material validation showed a very feasible category with percentages above 90%. The responses from teachers and students toward the media were also very positive, with a percentage of 86%. Effectiveness testing using N-Gain analysis indicated a high improvement in students’ reading literacy skills (N-Gain = 0.83). These findings suggest that interactive comic media is effective in enhancing students’ reading literacy skills and serves as an innovative and engaging alternative learning media in the digital era. The ADDIE model proved to be effective in developing learning media that is valid, practical, and effective for use in elementary schools.